If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + -2) = 2x Reorder the terms: (3 + x)(x + -2) = 2x Reorder the terms: (3 + x)(-2 + x) = 2x Multiply (3 + x) * (-2 + x) (3(-2 + x) + x(-2 + x)) = 2x ((-2 * 3 + x * 3) + x(-2 + x)) = 2x ((-6 + 3x) + x(-2 + x)) = 2x (-6 + 3x + (-2 * x + x * x)) = 2x (-6 + 3x + (-2x + x2)) = 2x Combine like terms: 3x + -2x = 1x (-6 + 1x + x2) = 2x Solving -6 + 1x + x2 = 2x Solving for variable 'x'. Reorder the terms: -6 + 1x + -2x + x2 = 2x + -2x Combine like terms: 1x + -2x = -1x -6 + -1x + x2 = 2x + -2x Combine like terms: 2x + -2x = 0 -6 + -1x + x2 = 0 Factor a trinomial. (-2 + -1x)(3 + -1x) = 0Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-2, 3}
| 3.428571429*14=x | | 1/4(x-3)=-2 | | 23000=mx+0.05 | | 5n-6n=18 | | 7(x-4)=16+32x | | 1/(2v^-2) | | an=550+(-50)(n-1) | | x^2+144=20 | | 1/2v-2 | | an=100+(-20)(n-1) | | 25x+x+3=90 | | 7x+1+108=180 | | -7/10+-5/12-1/4= | | 0.234=x/(0.000699-x) | | x^2+98x+64=0 | | 2(2x-5)=4x+10 | | y*25/52=5/13 | | 8sin^3x-cosx=0 | | .167=x/(.1497-x) | | 5x^2+35=24 | | 1.5*n=1.66 | | 8x+4.25=86 | | 7/4*y=21/4 | | an=-9+(-7)(n-1) | | x^4-4x^3-3x^2+10x+8=0 | | 15+x^2=120 | | 20x-16=15x+24 | | 2y-13y+5y=18 | | .234=x/(0.000699-x) | | 6=3x^2+3x | | N^2-n-40=0 | | 3x^2-18x+2=2 |